Impact of Servant Leadership, Self-Efficacy and Work Stress on Teachers’ Performance at Christian School - Listyani, Laras; Tung, Khoe Yao (Universitas Pendidikan Mandalika, 2024)
This study aims to analyze the effect of servant leadership, self-efficacy, and work stress on teachers’ performance. Aside from that, the study will also investigate if work stress can mediate the effect of servant leadership and self-efficacy on teachers’ performance. The approach used in this study is a quantitative approach, to confirm relationships between the variables. This is done by using a 36-person sample and a questionnaire modified from a number of other research. Data was collected by giving questionnaires to the teachers of a Christian High School and Middle School in Bandung. Then, the data was processed using Partial Least Square Structural Equation Modelling, by testing the validity and reliability first, and then testing the hypothesis. The result of this research shows that servant leadership has a positive effect on performance, although not significant. Meanwhile, self-efficacy has significant positive effect on performance. Work stress can affect performance negatively, although it wasn’t found to be significant in this study. For the mediation effect, work stress can mediate the positive effect of servant leadership and self-efficacy on performance, but not significantly. So in order to maintain or increase the quality of school, teachers need to have high self-efficacy level, and the school can help with that by mentoring and coaching, or other methods.